The Invention of pornography : obscenity and the origins of modernity, 1500-1800 - Hunt, Lynn, 1945- (ACLS Humanities E-Book., 1993)
"In this groundbreaking collection of essays, historians and literary theorists examine how, between 1500 and 1800, pornography emerged as a literary practice and a category of knowledge intimately linked to the formative moments of Western modernity and the democratization of culture. The first modern writers and engravers of pornography were part of the demimonde of heretics, freethinkers and libertines who constituted the dark underside of the Renaissance, the Scientific Revolution, the Enlightenment and the French Revolution. From the start, early modern European pornography used the shock of sex to test the boundaries and regulation of obscene behavior and expression in the public and private sphere. As such, pornography criticized and even subverted political authorities as well as social and sexual relations."--Jacket.